An Analysis of Students Emotions on Online Learning During Pandemic Covid-19 - Kurniasih, Dyan Nur; Suryaman, Maman (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Students are very vulnerable to emotional changes especially during this online learning method that caused by pandemic Covid-19. This change of learning method has resulted to students that students have to adapt to a new learning method that had several challanges in its implementation that caused some emotional unstable condition such as anxiety, stress, and depression. This issue becomes contemporary research in this area. Therefore this research paper is conducted to analyse the college students’ emotion on online learning during pandemic Covid-19. This research is a qualitative research with analytical descriptive approach. The research sample consisted of 6 students, the research was conducted in June 2021 on a sampling of 6 students from various state universities in Indonesia. The research instrument used a questionnaire from the google form website. The data were analyzed descriptively. The results showed that the majority of emotional problems experienced by students in the online learning process were anxiety. A total of 5 students experienced anxiety and stress, 3 students experienced depression. As a suggestion, several efforts can be made by students, families, and the government in reducing students’ unstable emotional conditions.